Determining the physical environment and safety influencers for active ageing and ageing-in-place in heritage city cores in the walled city of Jaipur, India - Rehal P.; Chani P.S.; Atreya S.; Kaur H. (My University, 2025)
Heritage cities exhibit a profoundly ingrained connection to historical and contemporary culture, offering inhabitants a distinct and unparalleled living experience. However, overcrowding, deterioration of built environments, and diminishing open spaces often become retardant forces for inclusiveness, active lifestyles, functional abilities and successful ageing-in-place among older adult residents. Given the foreseeable demographic trend of population ageing, there exists a notable scarcity of research in the context of Indian cities, particularly in the context of heritage urban regions, when compared to developed nations. The study examines the living conditions of heritage-built environments that influence the phenomenon of ageing-in-place within the Walled City of Jaipur City, India. The study employs a qualitative research methodology involving observational analysis in out-of-home environments and open-ended interviews among individuals 60 years and above selected through convenience sampling from the resident universal populations. The research findings reveal that deterioration of the neighbourhood-built environment, inadequate pedestrian conditions, and challenges to active mobility in heritage city cores are significant concerns for older adult residents. This paper advocates implementing planning policies that address the needs of ageing populations by prioritising improvements in out-of-home environments and pedestrian network connectivity amenities, which have universal benefits. © 2024 Informa UK Limited, trading as Taylor & Francis Group.